'Monster Scydmaenus' of Australia: revision of subgenus Corbulifer Franz (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2018)
The subgenus Corbulifer Franz of Scydmaenus Latreille is distributed along the east coast of the continental Australia. It was defined mainly on the basis of monstrously enlarged male metatibiae, which can be over twice as broad as femora. To date, two species (one with three subspecies) were known. Corbulifer is here revised and redefined, with characters not related to the male sexual dimorphism added to the diagnosis. Scydmaenus tamborinensis cunninghamensis Franz and S. tamborinensis maipotonensis Franz are placed as junior synonyms of S. tamborinensis Franz; S. pseudorobustus Franz is redescribed, and eight new species are described: S. monstrosetibialis sp. n., S. bellenderanus sp. n., S. kiwarrakianus sp. n., S. gushi sp. n., S. gibraltar sp. n., S. eungellanus sp. n., S. fishermontanus sp. n. and S. super sp. n.